2021
DOI: 10.3390/agronomy11112304
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ripening-Related Quality Traits of Long Shelf Life Tomatoes as Influenced by Water Deficit and Short-Term Postharvest Storage

Abstract: The diversity preserved within the European long shelf life tomato landraces (LSL) is a unique source to design high quality tomato products better adapted to changing environmental conditions and, thereby, to reduce food losses. The adaptation of LSL to water deficit (WD) management practices and their postharvest keeping ability can be used as tools to concomitantly enhance fruit quality and sustainable production. In this study, we investigated the effect of WD conditions and the plant growing environment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
3
4
0
Order By: Relevance
“…Our results have shown that the agro-environmental conditions traditionally adopted for the 'Piennolo' variety, which also include a "seccagna" (lack of irrigation) cultivation method, significantly increased SSC and redness while reducing FW and FIRM in both the 'Penjar-Ramellet' and 'Piennolo' groups. These effects of water deficit on fruit quality traits have been widely reported in the literature for the LSL tomato group [36,[54][55][56] and are similar to those described for tomatoes in general [24]. Taken together, our data show that the 'Piennolo' and 'Penjar-Ramellet' accessions analyzed in this study lost their peculiar phenotype when not cultivated in their original agro-environmental conditions.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results have shown that the agro-environmental conditions traditionally adopted for the 'Piennolo' variety, which also include a "seccagna" (lack of irrigation) cultivation method, significantly increased SSC and redness while reducing FW and FIRM in both the 'Penjar-Ramellet' and 'Piennolo' groups. These effects of water deficit on fruit quality traits have been widely reported in the literature for the LSL tomato group [36,[54][55][56] and are similar to those described for tomatoes in general [24]. Taken together, our data show that the 'Piennolo' and 'Penjar-Ramellet' accessions analyzed in this study lost their peculiar phenotype when not cultivated in their original agro-environmental conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the evolution of fruit color during the postharvest period, the 'Piennolo' (grown in Italy) and 'Penjar-Ramellet' (grown in Spain) groups showed a different pattern, the most important being the increase and the decrease in redness for the 'Penjar-Ramellet' and the 'Piennolo' groups, respectively. Moreover, a reduction in SSC, FIRM and FW was observed during postharvest in the 'Piennolo' group; this trend was also previously described in 'Penjar' landraces [36,41].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The occurrence of PG enzyme strongly associates with the onset of cell wall degradation. The natural synthesis of ethylene starts before the synthesis of PG enzyme and the exogenous ethylene that facilitate the accumulation of the enzyme in mature fruits (Grierson and Kader, 1986;Casals et al, 2021). The crop is characterized by remarkable post-harvest losses generally due to its high perishability and the poor storage conditions under which fruits are kept.…”
Section: Introductionmentioning
confidence: 99%